2023
DOI: 10.1039/d3qi01456h
|View full text |Cite
|
Sign up to set email alerts
|

Heteroanion-introduction-driven birefringence enhancement in oxychalcogenide Ba3MIIGe3O2S8 (MII = Mn, Cd)

Sheng-Hua Zhou,
Mao-Yin Ran,
Wen-Bo Wei
et al.

Abstract: Birefringent crystals play a crucial role in regulating the polarization of light and are widely used in optoelectronic fields. However, the effective design of novel infared (IR) birefringent crystals with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Secondly, we have observed that the [GeO x Q 4− x ] FBUs tend to exist largely independently within oxythiogermanate compounds. A notable exception to this trend is the compound Ba 3 M II Ge 3 O 2 S 8 (M II = Mn, Cd), 29 in which we have recently discovered the coexistence of [GeOS 3 ] and [GeO 2 S 2 ]. This simultaneous presence of different motifs is a relatively rare phenomenon within the context of [GeO 4 ]/[GeQ 4 ] and [GeO x Q 4− x ] FBUs.…”
Section: Resultsmentioning
confidence: 96%
“…Secondly, we have observed that the [GeO x Q 4− x ] FBUs tend to exist largely independently within oxythiogermanate compounds. A notable exception to this trend is the compound Ba 3 M II Ge 3 O 2 S 8 (M II = Mn, Cd), 29 in which we have recently discovered the coexistence of [GeOS 3 ] and [GeO 2 S 2 ]. This simultaneous presence of different motifs is a relatively rare phenomenon within the context of [GeO 4 ]/[GeQ 4 ] and [GeO x Q 4− x ] FBUs.…”
Section: Resultsmentioning
confidence: 96%
“…In other words, it is difficult to change the structures of these compounds under external forces and other factors. 29 Very recently, Lin et al reported two pentanary oxysulfides during our preparation of this manuscript, namely, Ba 3 M II Ge 3 O 2 S 8 (M II = Mn, Cd), 30 which have chemical compositions similar to those of 1 and 2. Ba 3 CdGe 3 O 2 S 8 (3) crystallizes in monoclinic P2 1 /n, different from orthorhombic Pnma for 1 and 2.…”
mentioning
confidence: 80%
“…215–228 This leads to distortions and the display of significant static dipole moments and anisotropy. 229–233 Unlike traditional chalcogenides, the presence of heteroanionic groups combines the high polarizability of chalcogenides with the advantages of oxides and halides that have wide E g . RE-based chalcohalides and oxychalcogenides not only incorporate disparate anions but also feature the presence of salt-inclusion compounds.…”
Section: Re-based Chalcogenides Containing Various Asymmetric Buildin...mentioning
confidence: 99%